2021
DOI: 10.46580/124367
|View full text |Cite
|
Sign up to set email alerts
|

Social media and COVID-19: A global study of digital crisis interaction among Gen Z and millennials

Abstract: The COVID-19 pandemic is revealing that global big tech platforms and social media are core sites for continuous engagement with crisis content for young citizens. This study included twenty-four countries from all continents at the time of the heightened COVID-19 crisis, and our survey targeted 18-40 year olds, Millennials and Gen Zs – overall n = 23,483 respondents. Outcomes show that for young citizens across continents, crisis communication is not just about press briefings. Instead, crisis communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 8 publications
2
39
0
4
Order By: Relevance
“…Increasing the availability of FP information through multiple channels is critical to reach wider audiences that may not have access to in-person services and address unmet FP needs, which has been linked to lack of credible and trusted sources of FP information among women (Sedgh et al, 2016 ). Mass media programmes have been effective in reaching wide audiences through common channels such as TV or radio, but have been linked to missing key groups due to issues with when programming is aired and accessible (Volkmer, 2021 ). We found that digital platforms provide flexibility in how and when FP information is accessed, accommodating groups that are seeking trusted FP information, but face physical barriers to tune in to a program at a specific time or finding time or resources to get to a clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the availability of FP information through multiple channels is critical to reach wider audiences that may not have access to in-person services and address unmet FP needs, which has been linked to lack of credible and trusted sources of FP information among women (Sedgh et al, 2016 ). Mass media programmes have been effective in reaching wide audiences through common channels such as TV or radio, but have been linked to missing key groups due to issues with when programming is aired and accessible (Volkmer, 2021 ). We found that digital platforms provide flexibility in how and when FP information is accessed, accommodating groups that are seeking trusted FP information, but face physical barriers to tune in to a program at a specific time or finding time or resources to get to a clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Health promotion strategies that use digital media to disseminate information have expanded rapidly in recent years (Volkmer, 2021 ). Where there is internet and smart phone access, digital media–an umbrella term that describes any methods of digital communication including texts, websites, social media apps, etc.–provides opportunities to remove barriers in accessing accurate sexual and reproductive health information and provides social networks online resources to share family planning (FP) information (Ochako et al, 2015 ; United Nations Population Fund, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The recent COVID-19 pandemic has changed the education strategies dramatically across the world [ 10 ]. The distinctive rise of e-learning being undertaken remotely has revolutionized the use of digital platforms and SNSs.…”
Section: Introductionmentioning
confidence: 99%
“…Social media created opportunities to keep people safe, informed and connected, and it exploded in popularity. 1 Information about which drugs to use and which to avoid could be rapidly spread, as well as what non-pharmacological strategies to engage in when managing COVID-19. Information about vaccines was also provided to medical practitioners and laypeople.…”
mentioning
confidence: 99%
“…Thus, we got to know about the role of hydroxychloroquine, angiotensin converting enzyme inhibitors (ACEIs), avoidance of non-steroidal anti-inflammatory drugs (NSAIDs), the debate around use of ivermectin for COVID-19 and correct assessment of symptoms of COVID-19. 1 , 2 , 3 , 4 Diagnostic criteria for COVID-19 and the value of using steroids in managing severe COVID-19 infections. Health professionals could also provide information to the public about what to do if infected and sick.…”
mentioning
confidence: 99%